The relationship between reactive depression and academic success among female students in Kuwait’s college of basic education - Al-Jasser, Lulwa Mutlaq (Edelweiss Applied Science and Technology, 2025)
This study explores the association of family support, educational environment, self-efficacy, and academic achievements with the intention of providing a different dimension to the factors affecting students’ performance. A quantitative survey method was used to analyze data using regression. Based on the findings, family support and self-efficacy transformed into a negative outcome towards success in academia, which means that when families are highly supportive, children may become overconfident, leading to poor performance. The educational environment, on the other hand, did not have any influence, thus showing how the generalized strategies adopted by institutions may not necessarily be the most ideal for students based on individual needs. These results contradict traditional views on the universally accepted outcomes of these factors, highlighting their contested and complicated roles in academic success. The contribution to theory is also significant as the study engages with contextually relevant perspectives and further seeks moderated variables for future examination. Practical implications are also highlighted, such as the need for families, educational institutions, and policies to implement balanced family engagement programs, self-regulation mechanisms, and specific educational contexts.